EFEKTIFITAS HIPNOTERAPI TERHADAP PENURUNAN MUAL MUNTAH PADA PASIEN KEMOTERAPI - Sulastri Sulastri; Nurul Huda; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Nausea and vomiting are side effects of cancer patients undergoing chemotherapy, and one of the ways to reducenausea and vomiting is by giving hypnotherapy. The aim of this study is to determine the effectiveness of hypnotherapyin decreasing nausea and vomiting by using the research designs; quasy experiment and one group pretest-postestdesign . There were 15 people taken as the samples of this research. They were taken based on the inclusion criteriausing purposive sampling technique. The measuring tool used in this research was Rhodes Index Nausea Vomiting(RINV) which has a scale of 0-5. The analyses used were univariate and bivariate analysis with Wilcoxon test. Based onthe results of the data analysis, it could be seen that there was a difference of nausea and vomiting scale before andafter hypnotherapy was given with p value (0.001) < α = 0.05, and there was a decrease in the scale of nausea andvomiting by 4.6. Therefore, it could be concluded that hypnotherapy is effective in decreasing the intensity of nauseaand vomiting of cancer patients. The result of the study is recommended to be used as a non-pharmacologicalintervention in hospitals.Keywords: Cancer, Chemotherapy, Hypnotherapy, Nausea and Vomiting